The Impact of Monetary Policy on Insolvency Risk at Vietnamese Commercial Banks (Global Journal of Management and Business Research, 2020)
The study assesses the impact of monetary policy on Vietnamese commercial banks' insolvency risk during the 2008-2017 period, with balanced panel data for 30 commercial banks in Vietnam. Results from the study show that an increase in the M2 money supply creates an increase in the Z index, which means a reduction in the risk of insolvency. The expansionary monetary policy increases real estate prices, collateral value, and bank capital, resulting in higher asset value for the bank. As a result, both deposit growth and credit growth in the economy have positive signs; therefore, the activity of commercial banks results in efficiency and improved profit, reducing the risk of insolvency. This result is consistent with the Borio and Zhu (2012) reports.
Keywords: monetary policy; insolvency risk; system GMM method